PERAN TEKNOLOGI KOMUNIKASI DALAM INTERAKSI AYAH DAN ANAK STUDI KASUS: INTERAKSI AYAH DAN ANAK MELALUI SMARTPHONE - Savitri, Detania (Informasi, 2015)
Function of a father is to support the finance of his family, while the mother functions as a nurturer for the child. A father that works full time will have his interaction with his child diminished. On the other side, communication technology has been developed to facilitate the interaction of individuals. This research aims to uncover if smartphones can increase the intensity and closeness of interaction between father and his children. Also, this research aims to know if fathers can socialize on his children through smartphones by controlling daily activities of the children. This article uses functionalism perspective. The author used qualitative approach by interviewing three fathers and three children aged 20 and up that currently use smartphones and residing in the city of Depok. The author finds that smartphones can alter the interaction between father and his children, and the father can provide social control to the children in interaction through smartphones. In interaction between father and children, smartphones can also be used father to socialize norms and values to his children in his interaction.Fungsi ayah dalam keluarga adalah sebagai pencari nafkah untuk memenuhi kebutuhan keluarga, sementara ibu berfungsi dalam mendidik anak. Ayah yang bekerja penuh waktu akan berkurang interaksinya dengan anak. Disisi lain, teknologi komunikasi diciptakan untuk mempermudah interaksi antar individu. Penelitian ini ingin mengetahui apakah smartphone dapat meningkatkan intensitas kedekatan interaksi antara ayah dan anak. Selain itu, penelitian ini juga ingin mengetahui apakah ayah dapat memberikan sosialisasi kepada anak melalui smartphone dan mengontrol keseharian anak. Artikel ini menggunakan perspektif fungsionalis. Pendekatan kualitatif digunakan oleh penulis dengan mewawancarai tiga ayah dan tiga anak berusia 20 tahun ke atas yang sama-sama menggunakan smartphone di kota Depok. Temuan yang diperoleh penulis yaitu smartphone dapat merubah interaksi ayah dengan anak, dan ayah dapat memberikan kontrol sosial kepada anak dalam interaksi melalui smartphone. Dalam interaksi ayah dan anak, smartphone juga dapat digunakan ayah untuk mensosialisasikan nilai-nilai kepada anak.